Reverse engineering : mechanisms, structures, systems, and materials - Messler, Robert W., Jr., 1942- (New York : McGraw-Hill Education, 2014)
'A comprehensive, fresh, and deservedly heightened look at reverse engineering as a legitimate approach to the learning and understanding to be gained from a design - a textbook for engineering students (taking required Intro to Engineering & Design and required Senior Design courses - especially for the subset of courses focused on Creative Design and Reverse Engineering) as they learn design and an on-the-job manual for practicing engineers engaged in design'--
Includes bibliographical references and index.
Keywords: Reverse engineering